2019
DOI: 10.1080/1744666x.2020.1693263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low tacrolimus exposure and high tacrolimus intra-patient variability on the development of de novo anti-HLA donor-specific antibodies in kidney transplant recipients

Abstract: van Gelder (2019) Impact of low tacrolimus exposure and high tacrolimus intra-patient variability on the development of denovo anti-HLA donor-specific antibodies in kidney transplant recipients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…Ten years ago Borra et al demonstrated that patients with high intra-patient variability more often reached a composite endpoint consisting of graft loss, biopsy-proven chronic allograft nephropathy, and 'doubling in plasma creatinine concentration in the period between t = 12 months post-transplantation and last follow-up' (Borra et al, 2010). A high intra-patient variability in tacrolimus exposure is now recognized as a predictor of poor clinical outcome (van Gelder, 2014;Mendoza Rojas et al, 2019). Rodrigo et al found that a higher intra-patient variability was independently related to development of donor-specific antibodies and graft-loss (Rodrigo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ten years ago Borra et al demonstrated that patients with high intra-patient variability more often reached a composite endpoint consisting of graft loss, biopsy-proven chronic allograft nephropathy, and 'doubling in plasma creatinine concentration in the period between t = 12 months post-transplantation and last follow-up' (Borra et al, 2010). A high intra-patient variability in tacrolimus exposure is now recognized as a predictor of poor clinical outcome (van Gelder, 2014;Mendoza Rojas et al, 2019). Rodrigo et al found that a higher intra-patient variability was independently related to development of donor-specific antibodies and graft-loss (Rodrigo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, therapeutic monitoring is required to ensure patients receive optimal exposure to the drug. Supratherapeutic tacrolimus concentrations may increase the risk of nephrotoxicity while subtherapeutic concentrations may increase the risk of antibody-mediated organ rejection over time (Sikma et al, 2015;Mendoza Rojas et al, 2019). Drug concentrations may also be altered by drug-induced PK changes.…”
Section: Pk/pd Variabilitymentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) is essential for achieving therapeutic trough concentrations. Despite the fact that monitoring blood trough concentrations is an effective method for adjusting tacrolimus oral doses, clinical studies have reported that it may not be valuable for future dosage estimation and may also not be an accurate assessment of overall drug exposure among various individuals [ 17 , 23 , 24 , 25 , 26 ]. It is sometimes challenging to achieve and maintain target tacrolimus trough concentrations despite periodic tacrolimus TDM [ 3 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
“…As discussed earlier, tacrolimus has a narrow therapeutic index and substantial inter-individual PK variability with standard weight-based dosing [ 56 , 57 ]. Moreover, tacrolimus also has a high intra-individual variability (IPV), resulting in sub-therapeutic and supra-therapeutic concentrations despite comparable dosing [ 25 ]. The coefficient of variation (CV) serves as a well-established biomarker of adherence in pediatric and adult groups of kidney transplant recipients [ 58 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
See 1 more Smart Citation